PENENTUAN BATASAN PARAMETER PERSAMAAN KEADAAN DYNAMIC DARK ENERGY (DDE) MENGGUNAKAN DATA SUPERNOVA TIPE IA - Nirmala Sari, Rahma
Various cosmological observations show that the universe is accelerating. One of the attempts to explain it is by adding dark energy. Cosmological constant () is the simplest model of dark energy and has been supported by many observations. However, there are problems adhere to cosmological constant, namely ne tuning and coincidence problems. To solve these problems and explain the accelerated expansion of the universe, several alternative models of dark energy have been proposed. This Final Project is repeating the work by Rahman (2020), i.e. determining dynamic dark energy equation of state (EoS) parameters using type Ia supernovae data, as well as studying the dependency of dynamic dark energy EoS parameters on the Hubble constant values. However, instead of using Union 2.1 dataset (Suzuki et al., (2012)), this Final Project employed Pantheon dataset provided by Scolnic et al. (2018). In studying the correlation of Hubble constant values and the EoS parameters value measured, the recent values of Hubble constant obtained from various techniques such as cosmic microwave background, baryonic acoustic oscillations, and distance ladder are used. The optimization procedures in this Final Project were performed using trust region method (TRM) with trust region re ective (TRF) and dogbox subproblems. The optimizations were applied to wCDM and CPL models, then to more complex JBP, BA, LH4, Pade-I, and Pade-II models to t dark energy density parameter and dynamic dark energy EoS parameters. Strong negative correlation is found between the xed Hubble constant values and the associated EoS parameter, w0. Furthermore BIC test was done for CDM and other DDE models, and it is concluded that CDM is the most supported model by SNe Ia.